CLOUD TECHNOLOGIES AND MODERN INFORMATION SYSTEMS (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
Cloud technologies have become a fundamental element of modern information systems and play a crucial role in the development of digital infrastructure. This article examines the theoretical foundations of cloud computing, its main service and deployment models, and its practical application in contemporary information technologies. Particular attention is paid to the efficiency of cloud services in data storage, processing, scalability, and system availability. Furthermore, the article analyzes information security issues, including data protection mechanisms, access control, and risk management in cloud environments. The study demonstrates that the effective implementation of cloud technologies contributes to the optimization of IT infrastructure, cost reduction, and the acceleration of digital transformation processes in both public and private sectors.